1984
DOI: 10.1148/radiology.153.2.6435169
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pulmonary ossification.

Abstract: Idiopathic pulmonary ossification is an uncommon and asymptomatic disorder of unknown etiology in which trabeculated bone is found in the lung. It is usually mistaken for more serious entities radiographically, most commonly appearing as branching linear shadows of calcific density involving a limited area of the lung and exhibiting very slow progression; however, the shadows may be round or irregular and bulky. Sometimes the trabeculae are recognizable, and occasionally the lungs demonstrate widespread involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…(6) Serum levels of calcium, phosphate, and alkaline phosphatase are normal.There is no evidence of parathyroid diseases or other conditions causing metastatic calcinosis. (4) Pulmonary function test results show a restrictive pattern, with a decrease in the diffusing capacity.The definite diagnosis is made through open lung biopsy. (6) Imaging results show reticular infiltrates of calcified density (dendriform type) throughout the bronchovascular distribution.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…(6) Serum levels of calcium, phosphate, and alkaline phosphatase are normal.There is no evidence of parathyroid diseases or other conditions causing metastatic calcinosis. (4) Pulmonary function test results show a restrictive pattern, with a decrease in the diffusing capacity.The definite diagnosis is made through open lung biopsy. (6) Imaging results show reticular infiltrates of calcified density (dendriform type) throughout the bronchovascular distribution.…”
Section: Discussionmentioning
confidence: 98%
“…(9) The histopathological type described herein is the dendriform pulmonary ossification one, also known as: pulmonary osteopathy, idiopathic disseminated pulmonary ossification, ossifying pneumonitis, bone metaplasia of the lung, racemose or reticular osteoplastic pulmonary disease, and arboriform ossification. (4,10) Dendriform pulmonary ossification is found associated with several conditions, such as histoplasmosis, chronic therapy with busulfan, pulmonary metastases of osteogenic sarcoma, pulmonary amyloidosis, areas of dystrophic calcifications, (1,11) and Goodpasture's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DPOs represent the less common form and are associated with pulmonary inflammation, pulmonary fibrosis, chronic obstructive pulmonary disease, asbestosis and pneumonia or may be idiopathic [3]. In a total of 1,393 adult autopsy cases performed by LARA et al [1], only eight were identified as having dendritic calcifications, an average of 0.6% of all adult autopsies or one case every 3 yrs.…”
Section: Nodular Pulmonary Ossifications In Differential Diagnosis Ofmentioning
confidence: 99%